Impact of School Plant on English Teachers Job Performance in Public Secondary School Federal Capital Territory, Abuja, Nigeria - Fatimayin, Foluke; Jacob, Ogunode Niyi (Universitas Syiah Kuala, 2022)
This study investigated impact of schools plant on English Teachers job performance and students academic performance in public secondary schools in FCT, Abuja, Nigeria. The study adopted a descriptive research design with a population of all the English language Teachers and English students in the public secondary schools in FCT. Simple random sampling technique was used to select 120 English Teachers and 300 English students (SS2). Questionnaire was adopted as data collection instrument. The instrument used to collect data was the Impact of School Plant on Teachers Job Performance and Student Academic Performance Questionnaire (ISPTJPQ). The questionnaire has sections A and B. Section A was on personal data of the respondents while section B provided answers to the research questions raised for the items on a modified Likert scale of measurement: Strongly agree (SA), agree (SA), disagree (D), Strongly disagree (SD). The reliability of the instrument was established through the test-retest method. The two sets of responses were correlated using Pearsons Product Moment Correlation and a reliability coefficient of 0.84 was obtained. Data collected were analysed using the mean, percentage, Pearsons Product Moment Correlation (r), Zero Differentiation Hypothesis statistical. The findings showed that there is significant relationship between school plant and English language teachers job performance in public secondary schools. The result also indicated that there is significant relationship between school plant and academic performance of students in public secondary schools.